Efficiency of Compressed Biomass Fuel from Water Hyacinth and Garlic Peel Using Corn Starch as a Binder - Chabumnet, Panlapa; Nillawat, Wanwisa; Jumrusprasert, Pattanapong (YRU Journal of Science and Technology, 2023)
Due to the widespread distribution of water hyacinth and garlic peel that are discarded from household industries, a development has been made to create benefits by using them to produce compressed biomass fuel and studying the properties of the compressed biomass fuel from water hyacinth and garlic peel using corn starch as a binder. The fixed ratio of water hyacinth and garlic peel in this research is 80:20, 60:40, 50:50, 40:60, and 20:80 by weight, with a constant ratio of binder. The compressed biomass fuel in this research is formed using the cold pressing method and then placed in a solar energy oven for 7 days. It was found that all ratios were able to form the fuel. The analysis of the properties of the compressed biomass fuel, such as moisture content, ash content, volatile matter content, fixed carbon content according to the ASTM D7582 standard, and calorific value according to the BSEN 14918 standard, revealed that the most efficient compressed biomass fuel is the ratio of water hyacinth to garlic peel of 20:80 by weight. It has the highest fixed carbon content at 13.54%, the highest volatile matter content at 71.07%, and the highest calorific value at 3,445 kcal/kg. The lowest ash content was 8.70%, indicating that it has a relatively high flammability. However, the fixed carbon content did not meet the standard requirement of at least 15%, so further research is needed to study methods to control moisture and improve the efficiency of the biomass fuel and the properties of the materials used to create a higher-quality compressed biomass fuel.